Kebijakan Pemerintah Daerah Dalam Membina Iklim Kerja pada Kantor Perwakilan Kabupaten Kepulauan Talaud di Manado - Mambo, Rully (JURNAL ADMINISTRASI PUBLIK, 2014)
Abstract :        The development of the conducive work climate to be a very important to push spirit of  work to increasing  performance remember that government bureaucracy working in the hierarchy environment, bureaucrats, monopoly and bound by the rules set consistently. Based on problem background has been analyzed, then can formulate problem how government policy region Talaud  Islands Regency in to develop work climate of representative office at Manado. Based on problem formulation then direction of research to know how policy implemented by the government of region Talaud Islands Regency in to develop work climate of representative office Talaud Islands Regency at Manado. This research treated and analyzed with use descriptive-analytic technique. Data source or respondent in this research is any civil servants representative office Talaud Islands Regency at Manado, number of civil servants placed in the representative office at Manado there are as many as 21 employees. Result data analysis above to give a conclusion that condition work climate in the representative office Talaud Islands Regency that exist today quite conducive and quite enjoyable and stimulating morale of the employees. Keywords : Implementation, work climate